The Effectiveness of School-Family Partnerships on Students' Character and Mental Recovery - Anggraini, Diana Noor; Sopianingsih, Pitria (Universitas PGRI Kanjuruhan Malang, 2023)
The reasoning and motivating to create this research by the low participation of the family and the community in supporting the academics of students. For this reason, it is necessary to have a school-family partnership to improve the quality of Indonesian education, one of which is on children's learning outcomes. This study was conducted to determine the effectiveness of the family-school partnership on on character and the mental recovery of students. The research was conducted using a survey method with the population in this study including students, parents, and teachers at junior high schools throughout the city of Bandung. So, the samples that can be taken are 434 junior high school students in Bandung City, 256 students' parents, and 51 teachers and school authorities. Data collection techniques using questionnaires and data analysis using percentage, correlation and regression techniques. The results of the study show that: 1) students display sufficient impacts such as stress in learning due to the Covid 19 pandemic; 2) The proposed form of school-family partnership is in the form of a digital network under the name SCOLA FAMILIA; 3) there is a significant influence between the implementation of school-family partnerships on student character and recovery. This shows the effectiveness of the family-school partnership on students' character and mental recovery.